Factors contributing to men's reluctance to seek HIV counselling and testing at Primary Health Care facilities in Vhembe District of South Africa - Pfungwa Mambanga; Robert N. Sirwali; Takalani Tshitangano (AOSIS, 2016)
Background: Voluntary HIV antibody Counselling and Testing (HCT) is a cornerstone of HIV prevention in South Africa because it has the potential to prevent HIV transmission. The government of South Africa has for a long time been investing heavily in fighting the spread of HIV and/or AIDS. However, men rarely utilise this service. Aim: The aim of this study was to explore the factors contributing to the reluctance of men to seek HCT in the primary health facilities in Vhembe District. Setting: The study was conducted at Vhembe District health offices in Limpopo, South Africa. Methods: A qualitative research design, anchored on semi-structured interviews as a method of data collection, was used. Fifteen men working at Vhembe health offices were purposively sampled. Data were analysed using the TECHS's 8 steps method. The approval from Polokwane Provincial offices was guaranteed with participants being protected and respected throughout the study. Results: The response rate per question was 100% with all 15 participants willing to answer all the raised questions though with different views and opinions. The majority of the interviewees indicated that they were aware of HCT services. Stigma as a societal reaction to disease, governmental policies, and attitudinal factors made men refrain from seeking counselling and testing from public health facilities. Conclusion: There was a high level of HCT awareness among men in Vhembe District. However, attitudinal and political barriers, stigma, and cultural practices such as circumcision were cited as the reasons for the low level utilisation of HCT services. Keywords: awareness, stigma, cultural practices, governmental politics, attitudinal factors